Recent development of Sino-Latin American relations and its implications - Jiang, Shixue (Estudios Internacionales, 2006)
As a developing country, China always considers its relations with other developing countries as the foundation of its foreign policies. It adheres to the principle of pursuing equality, mutual benefits, effectiveness and common development. Its relationship with Latin America and the Caribbean, dating back to a long time ago, is part of the South-South cooperation that has benefited both sides. In discussing Sino-Latin American relations, we note three factors, namely, the Latin American factor in China’s development, the China factor in Latin American development, and the U.S. factor in Sino-Latin American relations. Latin America is important for China economically, politically and diplomatically. China’s rise in the world stage has been making contributions to Latin America in many ways, and the Sino-Latin American relationship poses no threat to any third party.